Auditoría Informática al Departamento de Tecnología de la Información y Comunicación del Hospital Provincial General Docente Riobamba, Periodo 2018. - Tierra Álvarez, Jhonnatan Paul (2022)
The computer auditing has become an essential part for all organizations due to the increase in computers and information processing centers, therefore, the application of this helps to establish findings and reduce risks by implementing controls that allow the protection of important information and technological resources. The application of a computer auditing to the department of Information and Communication Technologies of the organizations helps to evaluate the quality standards through the fulfillment of the minimum requirements to achieve institutional excellence. The present graduated work seeks to determine the importance of computer auditing as a control tool in the Hospital General Docente of Riobamba city to determine the degree of regulatory compliance of internal control 410 Information Technology, as well as the use of computer equipment, for which the work has been divided into four chapters: within the first chapter the referential framework is disclosed as well as the problem of the investigation, later the hypothesis was formulated and what will be achieved with the present investigation, in the second chapter, the theoretical and conceptual framework about the organization are covered, as well as the dependent and independent variables, respectively. In the third chapter, it expresses the research methodology that is deductive, with a qualitative and quantitative approach, referring to population it was taken as a basis the staff of the different administrative departments of the entity which use computer equipment, in chapter four the execution of the audit is carried out, which consists of three phases, in the planning the visit to the facilities and the interview out to the head of the area were carried, and the respective surveys to the personnel of the entity, in the execution the internal control questionnaires were carried out and the respective evaluation of the level of trust, risk was elaborated and finally the sheet of findings was raised, in the communication it was made the final report auditing where it is explained the respective conclusions and recommendations to be taken into account by the management of the entity.